Dan Colen - Sweet liberty - Bonami, Francesco 1955-; Hansen, Blair (Other Criteria Books, 2017)
Sweet Liberty brings together 15 years of work by painter Dan Colen (born 1979), one of the 'bad boys' of the New York art world who emerged onto the scene in the early 2000s alongside artists like Dash Snow and Ryan McGinley. Witty, shocking, poignant and nihilistic, Colen's art presents a portrait of contemporary America and investigates the acts of producing and looking at art.0Alongside significant early works such as ?Me, Jesus and the Children? (2001-03), this publication features paintings from Colen's long-running Gum and Trash series, as well as four installations in which Colen appropriates imagery from the mass media and American subcultures. This volume marks, in Colen's own words, ?the first time I?ve been able to present the full range of my work and the wide-ranging ideas, crafts, materials, technologies and processes that I engage with. Exhibition: Newport Street Gallery, London, UK (04.10.2017- 21.01.2018)
Foreword by both Damien Hirst and Hugh Allan. Essays by Francesco Bonami & Blair Hansen. An interview with the artist by Ali Subotnick
Published on the occasion of the exhibition "Dan Colen - Sweet Liberty", 4.10.2017-21.1.2018, Newport Street Gallery, London
Keywords: Colen, Dan -- 1979-; Geschichte 2001-2016; Installation -- Kunst; Malerei; Ausstellungskatalog -- Newport Street Gallery -- 04.10.2017-21.01.2018 -- London; Bildband